Analisis Pelayanan Publik Pada Kelurahan Buliang Kecamatan Batu Aji Kota Batam - Milenisha Andani; Yunisa Oktavia (UIR Press, 2022)
This study aims to determine the public services of Buliang Village, Batu Aji District, Batam City. Because as it should be, public services are a series of activities carried out in order to meet the needs of the general public which of course have been stated in the State Constitution. The research here uses a descriptive method which is used in analysing public services in Buliang Village, located in Batu Aji District. The data collection technique used is by observing the community and analysing data collection from previous research. Based on the results of research analysis that has been obtained regarding public services in Buliang Village, Batu Aji District, it can be described through a community satisfaction, that most public services have not provided service satisfaction. However, this also does not rule out the possibility that the services provided are completely bad because there are still active efforts or actions, they take in trying to provide excellent public service satisfaction.